Challenging austerity: case law of the european court of justice on macroeconomic conditionality - Aymerich Cano, Carlos (Revista do Direito, 2020)
The EU’s response to the banking crisis unleashed in 2007, later turned into a public debt one, took place through the imposition of macroeconomic conditionality attached to the different bailout instruments. In summary, the measures imposed on the affected States through the corresponding Memorandum of Understanding (MoU) and Council Implementation Decisions (CID) consisted of social spending cuts - waves, allowances, pensions and public benefits; public spending on health, education and social services, etc. – as well as in the so-called structural reforms concerning the labor market, the pension system, the welfare and, between other areas, the financial sector. Actually, none of these measures were new: all of them were recommended, before the crisis outbreak, by EU institutions and other international organizations such as the OECD or the IMF. So the crisis offered a chance to confer binding force to those old recommendations or, in other word, to implement their “maximum” program.